Improved detection of preeruptive seismic velocity drops at the Piton de La Fournaise volcano. Issue 15 (15th August 2015) - Rivet, Diane; Brenguier, Florent; Cappa, Frédéric
Abstract The unexpected 2014 and 2015 Ontake (Japan) and Calbuco (Chile) eruptions proved that improving volcanic eruption prediction is still a great challenge. Decreases of seismic velocities of the Piton de la Fournaise volcano inferred from seismic noise correlations have been shown to precede eruptions. However, seismic velocities are strongly influenced by rainfall and subsequent pore pressure perturbations. Here we increase the detection of precursory seismic velocity changes to an eruption by removing the effects of pore pressure changes. During 2011–2013, the volcano exhibits a low eruptive activity during which we observe seismic velocity variations well correlated with rainfall episodes. We estimated the transfer function between fluid pressure and seismic velocity changes. We use these results to correct seismic velocity change time series for pore pressure changes, due to rainfall and found a preeruptive velocity drop (0.15%) associated with the 21 June 2014 eruption that was undetected before correction.